The Vital Role of Legal Education in Societal Transformation: Fostering Legal Awareness and Social Justice - Pradanna, Satrio Alpen; Irawan, Hendri (Contemporary Issues on Interfaith Law and Society, 2024)
This article explores the crucial role of legal education in societal transformation, with a specific focus on fostering legal awareness and promoting social justice. The introduction highlights the inherent interconnectedness of individuals in communal living and emphasizes law as a dual-aspect phenomenon governing legal subjects. The research aims to analyze the multifaceted functions of law, such as social control, engineering, symbolism, politics, and integration, to contribute to shaping a balanced and just society. The paper also delves into the objectives of legal education, intending to cultivate responsible citizens with a comprehensive understanding of legal awareness. Employing a qualitative approach through an extensive literature review, the methodology focuses on studying existing scholarly works. The article advocates for integrated efforts to realize legal transformation and societal harmony through robust legal education initiatives. In conclusion, it underscores the need for a collective commitment to fostering legal awareness for a more just and harmonious society